2021
DOI: 10.1096/fba.2021-00081
|View full text |Cite
|
Sign up to set email alerts
|

In vivo imaging of EVs in zebrafish: New perspectives from “the waterside”

Abstract: To harmoniously coordinate the activities of all its different cell types, a multicellular organism critically depends on intercellular communication. One recently discovered mode of intercellular cross-talk is based on the exchange of "extracellular vesicles" (EVs). EVs are nano-sized heterogeneous lipid bilayer vesicles enriched in a variety of biomolecules that mediate short and long-distance communication between different cells, and between cells and their environment.Numerous studies have demonstrated im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 116 publications
0
8
0
Order By: Relevance
“…And, a reciprocal EV-based crosstalk between muscle and bone has also been reported ( 317 ), highlighting the role of such vesicles, conserved among eukaryotes ( 318 ). Interestingly, zebrafish embryo-expressing fluorescent proteins associated with exosomes (e.g., CD63-phluorin) have been demonstrated to be a relevant model to study endogenous EVs in vivo to unravel fundamental aspects in EVs physiology and their role in inter-organ communication ( 319 , 320 ).…”
Section: New Approaches To Specific Analysis Of Tissue Interactionsmentioning
confidence: 99%
“…And, a reciprocal EV-based crosstalk between muscle and bone has also been reported ( 317 ), highlighting the role of such vesicles, conserved among eukaryotes ( 318 ). Interestingly, zebrafish embryo-expressing fluorescent proteins associated with exosomes (e.g., CD63-phluorin) have been demonstrated to be a relevant model to study endogenous EVs in vivo to unravel fundamental aspects in EVs physiology and their role in inter-organ communication ( 319 , 320 ).…”
Section: New Approaches To Specific Analysis Of Tissue Interactionsmentioning
confidence: 99%
“…Cancer-derived EVs can also function as drones to remotely suppress T-cell function through PD1-PD-L1 binding. , They also enhance the pro-tumorigenic functions of macrophages, which help circulating cancer cells exit blood vessels. A recent study found that cancer cell-derived EVs would be taken up by endothelial cells and macrophages after being injected into zebrafish embryos, leading to the activation of pro-metastasis macrophages in vivo . , …”
Section: Role Of Evs In Cancer Progression and Metastasismentioning
confidence: 99%
“…The study of endogenous EVs is tricky [ 69 ] and only partially translatable to mammalian models [ 70 , 71 ]; therefore, the most common approach for studying the biodistribution of EVs in vivo is injecting exogenous vesicles, isolated from conditioned cell culture media or biological fluids (plasma, urine, spinal fluid, saliva, etc.) [ 69 ].…”
Section: Molecular Imaging: a Tool To Study Ev Crosstalkmentioning
confidence: 99%